FILANTROPI SEBAGAI PREDIKTOR NILAI PERUSAHAAN MELALUI KINERJA KEUANGAN - Ng, Suwandi; Daromes , Fransiskus E.; Lukita, Merlin; Bangun, Yakobus K.; Lukman (Indonesian Journal of Accounting and Governance, 2020)
This research demonstrates that philanthropic activity is a predictor of firm value through financialperformance. The population used is all non-financial companies listed on the Indonesia StockExchange (BEI) for the 2015-2018 period. The number of samples is 101 companies each year, whichwere selected by purposive sampling method. The results of this study indicate that philanthropy has asignificant effect on financial performance but not significant on firm value. However, another findingreveals that financial performance has a significant effect on firm value. Based on Sobel's test results,it shows that financial performance mediates the effect of philanthropy on firm value.